Combining reactive sputtering and rapid thermal processing for synthesis and discovery of metal oxynitrides. Issue 19 (27th May 2015) - Zhou, Lan; Suram, Santosh K.; Becerra-Stasiewicz, Natalie; Mitrovic, Slobodan; Kan, Kevin; Jones, Ryan J.R.; Gregoire, John M.
Abstract: Abstract : Recent efforts have demonstrated enhanced tailoring of material functionality with mixed anion materials, yet exploratory research with mixed anion chemistries is limited by the sensitivity of these materials to synthesis conditions. Synthesis of a particular metal oxynitride compound by traditional reactive annealing requires specific, limited ranges of both oxygen and nitrogen chemical potentials to establish equilibrium between the solid-state material and a reactive atmosphere. Using Ta–O–N as an example system, we describe a combination of reactive sputter deposition and rapid thermal processing (RTP) for synthesis of mixed anion inorganic materials. Heuristic optimization of reactive gas pressures to attain a desired anion stoichiometry is discussed, and the ability of RTP to enable amorphous to crystalline transitions without preferential anion loss is demonstrated through the controlled synthesis of nitride, oxide, and oxynitride phases.